Răspuns :
1). 2√3·(√5-1)(√5+1)+(2√3-5)²+(3√3+2)²=2√3(√5²-1²)+12-20√3+25+27+18√3+4=
=8√3+12-20√3+25+27+18√3+4=6√3+68
2). Pe prima o raționalizezi, la fel și pe celelalte cu radical, apoi aduci la același numitor și calculezi.
=8√3+12-20√3+25+27+18√3+4=6√3+68
2). Pe prima o raționalizezi, la fel și pe celelalte cu radical, apoi aduci la același numitor și calculezi.
1). 2√3·(√5-1)(√5+1)+(2√3-5)²+(3√3+2)²=2√3(√5²-1²)+12-20√3+25+27+18√3+4=
=8√3+12-20√3+25+27+18√3+4=6√3+68
=8√3+12-20√3+25+27+18√3+4=6√3+68